Root stress and nitrogen deposition consequences and research priorities - Smithwick, Erica A H (The New phytologist, 2013)
Stress within tree roots may influence whole-tree responses to nutrient deficiencies or toxic ion accumulation, but the mechanisms that govern root responses to the belowground chemical environment are poorly quantified. Currently, root production is modeled using rates of forest production and stoichiometry, but this approach alone may be insufficient to forecast variability in forest responses when physical and chemical stressors alter root lifespan, rooting depth or mycorrhizal colonization directly. Here, we review key research priorities for improving predictions of tree responses to changes in the belowground biogeochemical environment resulting from nitrogen deposition, including: limits of the optimum allocation paradigm, root physiological stress and lifespan, contingency effects that determine threshold responses across broad gradients, coupled water-biogeochemical interactions on roots, mycorrhizal dynamics that mediate root resilience and model frameworks to better simulate root feedbacks to aboveground function. We conclude that models incorporating physiological feedbacks, dynamic responses to coupled stressors, mycorrhizal interactions, and which challenge widely-accepted notions of optimum allocation, can elucidate potential thresholds of tree responses to biogeochemical stressors. Emphasis on comparative studies across species and environmental gradients, and which incorporates insights at the cellular and ecosystem level, is critical for forecasting whole-tree responses to altered biogeochemical landscapes